Low valent aluminum and gallium compounds: structural variety and coordination modes to transition metal fragments - Linti, Gerald W.; Schnöckel, Hansgeorg (Coordination chemistry reviews, 2000)
The chemistry of low valent aluminum and gallium compounds is a very topical area of research. Accompanying the preparative challenge in synthesizing …